Florida Herbicide Pricing and Expectations - Mark A. Mossler (EDIS, 2006)
PI-137, a 2-page fact sheet by M. A. Mossler, is a list of herbicide active ingredients and their prices, compiled from various sources. Published by the UF Pesticide Information Office, October 2006.